Design and Evaluation of Photo-Induced Biofeedback Fabric for the Enhancement in Sleeping Sense - Wei-Cheng Chu; Hsin-Ju Lin; Shu-Ping Chiu (Advances in Materials Science and Engineering)
Based on overcoming the sleeping obstacle for people, the purpose of this study is to design a photo-induced biofeedback fabric which is a kind of optical fiber fabric with the function of enhancing sleeping sense and to evaluate its effect. The fabrics with two layers including background layer and pattern layer were designed firstly. The pattern layers with 3 kinds of wavelengths of sine waves and the light controller with 3 kinds of flashing frequencies were then prepared. Guiding the light into the optical fiber, it will emit out of the optical fiber and stimulate our visual system to change the form of brain wave. Finally, EEG and sleeping scale were applied to evaluate the effect of enhancing sleeping sense. The results were shown that human’s brain wave can be changed from sober status to shallow-sleeping status and the effect of enhancing sleeping sense can be achieved for all pattern layers in frequencies of 0, 5 and 10 Hz. Furthermore, female is more significant than male and participants age from 30 to 49 are the most significant. Besides, the stronger the participant’s stress is, the more significant the sleeping sense is.